The Role of the Financial Control in Regulating the Government Spending in Kuwait - Al Mutairi , Sattam A. M (Remah Review for Research and Studies, 2021)
This study explored the role of the financial control in regulating the government spending in Kuwait. The researcher adopted a descriptive analytical approach. The population consists from all the administrators in the top and middle administrative levels who work in the ministries in Kuwait. A non-proportionate sampling method was used for choosing a sample consisting from 150 individuals. The forms of the questionnaire were passed to those individuals. 131 valid forms were retrieved. The researcher found that financial control has a statistically significant impact on regulating the government spending in Kuwait. The efficiency of the financial control has a statistically significant impact on regulating the government spending in Kuwait. The effectiveness of the financial control has a statistically significant impact on regulating the government spending in Kuwait. The researcher provided several recommendations. For instance, he recommends activating the role of the control bodies and tools in enforcing control over the standards used for assessing the spending programs. He recommends holding courses and international and national seminars for holding discussions about rationalizing the expenditures and enforcing control over them. He recommends providing more attention by the financial controller to the process of enforcing control over examining and assessing projects. That shall contribute to ensuring the feasibility of projects.